ANALISIS FAKTORKEHADIRAN MAHASISWA TERHADAP PROSES BELAJAR MENGAJAR MENGGUNAKAN METODE PRINCIPLE COMPONENT ANALYSIS - Hermawaty Hermawaty (CCIT Journal, 2019)
The teaching and learning process in lectures is very much determined by the presence of students and lecturers. There are regulations made by lecturers and agreed upon by students so that there is discipline and comfort in the learning atmosphere. One of the causes of lack of discipline in the classroom is that there is a delay in students in attending lectures, this makes the learning atmosphere less comfortable because the concentration of other students is disturbed. From this problem the writer is interested in conducting research by raising the title "analysis of student attendance factors on the teaching and learning process using the principle component analysis method.The research method used is by conducting preliminary research, formulating problems and processing data using SPSS software, then by testing the barttley test. The results of this study are expected to be able to find out the variables causing the low attendance of students, so that lecturers can make regulations that are more assertive and agreed upon by students